Modelling Universal Basic Income using UKMOD - Jerome De Henau; Susan Himmelweit; Sara Reis (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2021)
This paper focuses on the possibilities and functionalities offered by the tax-benefit microsimulation model for the UK – UKMOD to simulate and analyse the distributional impact of three examples of Basic Income schemes. We show how to build in functionalities to ensure fiscal neutrality and we aim to highlight some of the trade-offs that implementing a Basic Income scheme brings. This paper doesn't intend to engage with arguments around the desirability of introducing Basic Income but rather focuses on the options that UKMOD offers, giving a couple of examples of schemes based on a set of criteria described below.
Keywords: 330; Income Dynamics; Public Policy; Welfare Benefits; Taxation; Microsimulation; Households